2020
DOI: 10.1200/go.20.00319
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience of Treating Children and Young Adults With Image-Guided Proton Beam Therapy in India

Abstract: PURPOSE Proton beam therapy (PBT) has been a preferred modality in pediatric malignancies requiring radiotherapy. We report our preliminary experience of treating consecutive patients younger than 25 years with image-guided pencil beam scanning PBT from the first and only center on the Indian subcontinent. METHODS Patients were selected for PBT on the basis of a multidisciplinary tumor board decision. Patient demographic data, as well as tumor and treatment-related characteristics of the cohort, were captured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As a rst modern proton therapy centre in South East Asia, we treated more than 500 patients over past two years and CNS tumours constituted maximum bulk of it. We have reported our preliminary experience in children and young adults (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…As a rst modern proton therapy centre in South East Asia, we treated more than 500 patients over past two years and CNS tumours constituted maximum bulk of it. We have reported our preliminary experience in children and young adults (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…As a first modern proton therapy centre in South East Asia, we treated more than 500 patients over past two years and CNS tumours constituted maximum bulk of it. We have reported our preliminary experience in children and young adults [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…This is possible due to superior dose conformity and lower normal tissue dose, offering better Quality of Life (QoL) for childhood cancer patients and survivors [24]. Chilkuri et al demonstrated a low incidence of grade 3 acute toxicities despite a median dose of 54 CGE for CNS tumours with overall, 62%, 26%, and 0% of patients having grade 1, grade 2, and grade 3 fatigue, respectively [25].…”
Section: Radiation Therapymentioning
confidence: 99%